Direct evidence for a predominantly exolytic processive mechanism for depolymerization of heparin-like glycosaminoglycans by heparinase I - Ernst, Steffen (The National Academy of Sciences, 1998)
Heparinase I from Flavobacterium heparinum has important uses for elucidating the complex sequence heterogeneity of heparin-like glycosaminoglycans (HLGAGs). Understanding the biological function of HLGAGs has been impaired by the limited methods for analysis of pure or mixed oligosaccharide fragments. Here, we use methodologies involving MS and capillary electrophoresis to investigate the sequence of events during heparinase I depolymerization of HLGAGs. In an initial step, heparinase I preferentially cleaves exolytically at the nonreducing terminal linkage of the HLGAG chain, although it also cleaves internal linkages at a detectable rate. In a second step, heparinase I has a strong preference for cleaving the same substrate molecule processively, i.e., to cleave the next site toward the reducing end of the HLGAG chain. Computer simulation showed that the experimental results presented here from analysis of oligosaccharide degradation were consistent with literature data for degradation of polymeric HLGAG by heparinase I. This study presents direct evidence for a predominantly exolytic and processive mechanism of depolymerization of HLGAG by heparinase I.